Unraveling the Complex Nexus of Macrophage Metabolism, Periodontitis, and Associated Comorbidities - Zihan Zhang; Yi Liu; Tian Yu; Zhen Liu (Journal of Innate Immunity)
Background: Periodontitis is recognized as one of the most prevalent oral dysbiotic inflammatory diseases, ultimately leading to the irreversible destruction of periodontal tissues. Macrophages play a pivotal role in the development and progression of periodontitis, and the feasibility of targeting them therapeutically has been established. Since metabolic switching significantly contributes to macrophage regulation, conducting an in-depth review of macrophage metabolism in periodontitis may serve as the foundation for developing innovative treatments. Summary: This paper has been carefully reviewed to provide a comprehensive overview of the roles played by macrophages in periodontitis and associated comorbidities. Initially, detailed presentations on the metabolic reprogramming of macrophages, including glucose, lipid, and amino acid metabolism, were provided. Subsequently, dominating macrophage phenotype and metabolism under lipopolysaccharide (LPS) stimulation or during periodontitis were presented with emphasize on critical molecules involved. Furthermore, in recognition of the close association between periodontitis and several comorbidities, the interaction among macrophage metabolism, periodontitis, and related metabolic diseases, was thoroughly discussed. Key Messages: Through the examination of current research on macrophage metabolic reprogramming induced by periodontitis, this review provides potential immunometabolic therapeutic targets for the future and raises many important, yet unstudied, subjects for follow-up. Background: Periodontitis is recognized as one of the most prevalent oral dysbiotic inflammatory diseases, ultimately leading to the irreversible destruction of periodontal tissues. Macrophages play a pivotal role in the development and progression of periodontitis, and the feasibility of targeting them therapeutically has been established. Since metabolic switching significantly contributes to macrophage regulation, conducting an in-depth review of macrophage metabolism in periodontitis may serve as the foundation for developing innovative treatments. Summary: This paper has been carefully reviewed to provide a comprehensive overview of the roles played by macrophages in periodontitis and associated comorbidities. Initially, detailed presentations on the metabolic reprogramming of macrophages, including glucose, lipid, and amino acid metabolism, were provided. Subsequently, dominating macrophage phenotype and metabolism under lipopolysaccharide (LPS) stimulation or during periodontitis were presented with emphasize on critical molecules involved. Furthermore, in recognition of the close association between periodontitis and several comorbidities, the interaction among macrophage metabolism, periodontitis, and related metabolic diseases, was thoroughly discussed. Key Messages: Through the examination of current research on macrophage metabolic reprogramming induced by periodontitis, this review provides potential immunometabolic therapeutic targets for the future and raises many important, yet unstudied, subjects for follow-up.